PESANTREN SAINS: EPISTEMOLOGY OF ISLAMIC SCIENCE IN TEACHING SYSTEM - Mohamad Yasin Yusuf (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
Muslims around the world mostly was under the domination of the West in the mastery of science and technology. Establishing educational institutions that are based on science and technology is one of the ways to solve the problem.This study had the purpose to examine the epistemology of science in the teaching system in SMA Trensains boarding school Tebuireng Jombang. Applying the method of field research through qualitative approach and philosophical analyses, this study revealed that SMA Trensains Tebuireng Jombang applied